The Impact of Using Blackboard on Student’s Grades - Alshmasi, Dalia; Alharbi, Jawaher; Alhothly, Nada (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The Learning Management System (LMS) is a core system that contributes to support e-learning, managing content, provide learning tools, and facilitate communication between students and teachers. This project aims to measure the impact of Blackboard-based e-learning use. We measure the effect of blackboard use on male students by comparing male and female students ’degrees of online learning (online class preparation) and traditional (face-to-face) learning at Qassim University, using statistical methods and data mining algorithms. We also develop A supportive tool that helps teachers manage some important tasks such as (student attendance, interaction, grades ... etc.). This tool will take student information and push automatic notifications to all concerned people via SMS.